Random forests estocástico - Gómez, Silvio Normey (2012)
In the Data Mining area experiments have been carried out using Ensemble Classifiers. We experimented Random Forests to evaluate the performance when randomness is applied. The results of this experiment showed us that the impact of randomness is much more relevant in Random Forests when compared with other algorithms, e.g., Bagging and Boosting. The main purpose of this work is to decrease the effect of randomness in Random Forests. To achieve the main purpose we implemented an extension of this method named Stochastic Random Forests and specified the strategy to increase the performance and stability combining the results. At the end of this work the improvements achieved are presented